How does women’s time in reproductive work and agriculture affect maternal and child nutrition? Evidence from Bangladesh, Cambodia, Ghana, Mozambique, and Nepal - Komatsu, Hitomi; Theis, Sophie; Malapit, Hazel J. (International Food Policy Research Institute, 2015)
There are concerns that increasing women’s engagement in agriculture could have a negative effect on nutrition because it limits the time available for nutrition-improving reproductive work. However, very few empirical studies have been able to analyze whether these concerns are well-founded. This paper examines whether an increase in women’s time in agriculture adversely affects maternal and child nutrition, and whether the lack of women’s time in reproductive work leads to poorer nutrition. Using data from Bangladesh, Cambodia, Ghana, Mozambique, and Nepal, we find that on the whole, in poor households, reductions in women’s reproductive work time are detrimental to nutrition, especially for children. In contrast, women’s and children’s nutrition in nonpoor households is less sensitive to reductions in time on reproductive work. Working long hours in agriculture reduces women’s dietary diversity score in Ghana and nonpoor women’s in Mozambique. However, for poor women and children in Mozambique, and children in Nepal, working in agriculture in fact increases dietary diversity. This suggests that agriculture as a source of food and income is particularly important for the poor. Our results illustrate that women’s time allocation and nutrition responses to agricultural interventions are likely to vary according to socioeconomic status and local context.